(untitled) (Asian Education Studies, 2016)
Since reading achievement is a determining factor for academic success, children who struggle with reading often continue to struggle throughout their school careers. The purpose of this study was to compare the reading gain scores of fourth and fifth grade students at an elementary school in northeast Alabama to the quantity of their extracurricular reading activities, controlling for gender, ethnicity, and socioeconomic status (SES). Over a 20-week period, the researcher utilized a daily reading log as the instrument to determine the amount of students’ outside-of-school reading time engagement. The results of a factorial ANOVA indicated that the amount of out-of-school reading times did not significantly increase their gain scores on the STAR reading benchmark tests. This was true for gender, socioeconomic status, and race. The results have implications for utilization of out-of-school reading requirements.